Diagnosis of Heart Disease using Cultural Algorithm with Neural Network - Shrivastava, S; Shrivastava, S (International Journal of Computer Sciences and Engineering, 2018)
Heart disease detection is considered as the most complicated task in the world of medical sciences. There arises a necessity to progress the work and to develop a decision support system to find out a heart disease of a patient. To achieve a correct and cost effective treatment computer-based and support systems can be developed to make good decision. These information which exists contains the huge amounts of data which are organized in the form of images, text, charts and numbers. Hence, there is necessity which is motivating to create an excellent and useful project which will help physicians and cardiologists to predict the heart disease before it damage the health. It can be able to solve complicated enquiries for detecting heart disease in a patient and as a result it will assist medical practitioners to make more accurate and precise clinical decisions which traditional decision support systems were not able to decide. By providing effective and respective solution, it will surely help to reduce costs of treatment.